2010
DOI: 10.1002/hipo.20891
|View full text |Cite
|
Sign up to set email alerts
|

Mu opioid receptor mRNA expression, binding, and functional coupling to G‐proteins in human epileptic hippocampus

Abstract: Mu opioid receptors (MOR) are known to be involved in seizure activity. The main goal of the present study was to characterize the MOR mRNA expression, binding, as well as G protein activation mediated by these receptors in epileptic hippocampus of patients with pharmacoresistant mesial temporal lobe epilepsy (TLE). In contrast with autopsy samples, hippocampus obtained from patients with mesial TLE demonstrated enhanced MOR mRNA expression (116%). Saturation binding experiments revealed significantly higher (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The evaluation of IL-1β and IL-6 levels in brain tissue (neocortex) of patients with DRTLE showed values that indicate the presence of an inflammatory process at the central level reinforced by the absence of these markers in the control tissue. Tissue obtained at autopsy from subjects with no evidence of neurological disease was used as controls since previous reports indicate that proteins from brain tissue are preserved for several hours after death [ 28 , 29 , 30 , 49 ]. Previously, other authors supported the nondetection of concentrations of proinflammatory cytokines in the brain tissue of control subjects [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of IL-1β and IL-6 levels in brain tissue (neocortex) of patients with DRTLE showed values that indicate the presence of an inflammatory process at the central level reinforced by the absence of these markers in the control tissue. Tissue obtained at autopsy from subjects with no evidence of neurological disease was used as controls since previous reports indicate that proteins from brain tissue are preserved for several hours after death [ 28 , 29 , 30 , 49 ]. Previously, other authors supported the nondetection of concentrations of proinflammatory cytokines in the brain tissue of control subjects [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The μOR system (both μORs and the endogenous ligand, enkephalin) is altered in both epilepsy (Laorden et al, 1985; Gall, 1988; Gall et al, 1988; D’Intino et al, 2006; Rocha et al, 2007; Cuellar-Herrera et al, 2010) and Alzheimer’s disease (Meilandt et al, 2008). In fact, it was shown that the increase in enkephalin in a model of Alzheimer’s contributed to the cognitive difficulties associated with the disease (Meilandt et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Acute and chronic opioid administration affects CA1 function and plasticity (Mansouri et al, 1997; Wagner et al, 2001), and the hippocampal μ opioid receptor (μOR) system is altered in epilepsy and Alzheimer’s disease (Gall, 1988; Meilandt et al, 2008; Cuellar-Herrera et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, μ-opioid receptor knock-out mice show reduced radial-arm maze and Morris water maze performance (Jamot et al, 2003). Further, alterations in the hippocampal opioid system are also seen, for example, in epilepsy and Alzheimer’s, indicating a potential role in these disorders (Laorden et al, 1985; Gall, 1988; Gall et al, 1988; D’Intino et al, 2006; Rocha et al, 2007; Cuellar-Herrera et al, 2012). Moreover, in a model of Alzheimer’s it was found that the reported increase in enkephalin (an endogenous ligand for μ-opioid receptors) contributed to the cognitive difficulties associated with the disease (Meilandt et al, 2008), indicating that changes in the hippocampal opioid system can have significant functional consequences.…”
Section: Neuromodulators and Neurogliaform Family Cellsmentioning
confidence: 99%